Impact of ETNK1 somatic mutations on phosphoethanolamine synthesis, ROS production and DNA damage. (4th March 2021) - Fontana, Diletta; Gambacorti-Passerini, Carlo; Piazza, Rocco
ABSTRACT: Recently we showed that Ethanolamine Kinase 1 ( ETNK1) mutations cause a decreased synthesis of phosphoethanolamine, and that phosphoethanolamine is able to modulate mitochondrial activity through competition with succinate for complex II. The decreased phosphoethanolamine concentration leads to increased mitochondria activity and reactive oxygen species production, which causes the accumulation of new mutations.